DIGITAL TECHNOLOGIES AS A TOOL FOR IMPROVING THE EFFECTIVENESS OF UKRAINE’S SOCIAL PROTECTION SYSTEM - Moysiyaha, Andriy (Public Management and Policy, 2026)
The article analyzes digital technologies as a tool for increasing the efficiency of the social protection system of Ukraine. In accordance with the purpose of the study, it is determined that the digitalization of social protection should be considered not as a set of separate electronic services, but as a holistic integrated system, within which electronic channels of appeal, interoperability of registers, a single information environment, data management mechanisms and performance monitoring tools are combined. It was found that in the international discourse, the effectiveness of digitalization is associated with the full chain of social service provision - from informing and registration to the appointment of assistance, support and evaluation of effectiveness. The approaches of the World Bank Group and the Organization for Economic Co-operation and Development are considered, which emphasize the importance of administrative data integration, automation of procedures, hybrid access models and reducing barriers for beneficiaries. The current state of the digital transformation of social protection in Ukraine is characterized, which is characterized, on the one hand, by the development of the “Diya” platform, the “Trembita” infrastructure, the EISSS and portal services, and on the other hand, by the presence of systemic limitations related to data quality, fragmentation of registers, digital inequality, protection of personal information and the lack of a standardized KPI system. It is proven that the implementation of AI/ML and Big Data in back-office processes, the use of blockchain solutions in niche scenarios of humanitarian coordination, as well as the formation of a public system for monitoring the effectiveness of digitalization, are promising areas of development. The conclusions are drawn that digital technologies acquire real managerial potential only under conditions of system integration, institutional coherence, legal certainty, inclusive access and proper cyber protection. Digitalization of social protection in Ukraine has the potential to become an effective tool for increasing the efficiency, accuracy, security and fairness of social support; however, its effectiveness directly depends on the completion of the institutional deployment of the EISSS, data standardization and the implementation of a multidimensional assessment system.